Foreword to the special issue on 3D object retrieval 2021 workshop (3DOR2021). (February 2022) - Biasotti, Silvia; Dyke, Roberto M.; Lai, Yu-Kun; Rosin, Paul L.; Veltkamp, Remco
Highlights: Foreword to the 14th Eurographics workshop on 3D Object Retrieval (3DOR2021). Research into methods and evaluation techniques for shape retrieval are presented. A total of 17 papers were submitted to C&G, of which 11 were accepted.